2014
DOI: 10.5194/npg-21-1075-2014
|View full text |Cite
|
Sign up to set email alerts
|

Wavevector anisotropy of plasma turbulence at ion kinetic scales: solar wind observations and hybrid simulations

Abstract: Abstract. Wavevector anisotropy of ion-scale plasma turbulence is studied at various values of ion beta. Two complementary methods are used. One is multi-point measurements of magnetic field in the near-Earth solar wind as provided by the Cluster spacecraft mission, and the other is hybrid numerical simulation of two-dimensional plasma turbulence. Both methods demonstrate that the wavevector anisotropy is reduced with increasing values of ion beta. Furthermore, the numerical simulation study shows the existenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
(40 reference statements)
2
10
0
Order By: Relevance
“…This basic notion can be summarized as follows. MHD fluctuations in the solar wind reveal distinct anisotropies in the fieldamplitude variances and energy spectra in the inertial range and ion dissipation range (Horbury et al 2012;Comişel et al 2014). Similar wave vector anisotropies are obtained in simulated and modeled turbulence energy spectra.…”
Section: Quasi-perpendicular Propagationsupporting
confidence: 53%
“…This basic notion can be summarized as follows. MHD fluctuations in the solar wind reveal distinct anisotropies in the fieldamplitude variances and energy spectra in the inertial range and ion dissipation range (Horbury et al 2012;Comişel et al 2014). Similar wave vector anisotropies are obtained in simulated and modeled turbulence energy spectra.…”
Section: Quasi-perpendicular Propagationsupporting
confidence: 53%
“…Other studies, including those employing the multi-spacecraft k-filtering technique [68,69], have also found that the quasi-perpendicular wavevectors remain energetically dominant in the dissipation range [67,[70][71][72][73][74][75], as in the inertial range. In k-filtering, multi-spacecraft observations (e.g.…”
Section: (A) Review Of Observationsmentioning
confidence: 99%
“…Generally all of the incompressible points follow the empirical law obtained in Comişel et al (2014). In the two intervals of fast solar wind, the compressible magnetic fluctuations are the most anisotropic followed by the incompressible magnetic fluctuations and the most isotropic being the density fluctuations.…”
Section: Anisotropymentioning
confidence: 59%
“…The dashed line in Fig. 2a denotes the empirical relation derived from the numerical simulations of Comişel et al (2014), and the dot dashed line at A = 1 denotes isotropy. It is important to note that this relation was derived for the total magnetic field fluctuations and were performed over a plasma β range of [0.05, 2].…”
Section: Anisotropymentioning
confidence: 99%